1985
DOI: 10.1103/physrevlett.54.224
|View full text |Cite
|
Sign up to set email alerts
|

Prism-Coupled Light Emission from Tunnel Junctions

Abstract: We have observed completely p-polarized light emission from smooth Al-A10"-Au tunnel junctions placed on a prism coupler. The angle and polarization dependence demonstrate unambiguously that the emitted light is radiated by the fast-mode surface plasmon polariton. The emission spectra suggest that the dominant process for the excitation of the fast mode is through conversion of the slow mode to the fast mode mediated by residual roughness on the junction surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…SPP cross-coupling was discussed theoretically by Weber and Mills, 8 and there followed a number of further reports. 9,10 Ushioda et al 11 invoked roughness mediated cross-coupling to explain some of their results on light emitting tunnel junctions but it was Gruhlke et al 12 who first reported the emission of light generated by molecular fluorescence through a corrugated metal film mediated by SPP cross coupling in 1986. The transmission of light through nanostructured metallic films received renewed interest following the report in 1998 by Ebbesen and co-workers 13 of enhanced transmission through metallic films perforated with periodic arrays of subwavelength holes.…”
Section: Introductionmentioning
confidence: 99%
“…SPP cross-coupling was discussed theoretically by Weber and Mills, 8 and there followed a number of further reports. 9,10 Ushioda et al 11 invoked roughness mediated cross-coupling to explain some of their results on light emitting tunnel junctions but it was Gruhlke et al 12 who first reported the emission of light generated by molecular fluorescence through a corrugated metal film mediated by SPP cross coupling in 1986. The transmission of light through nanostructured metallic films received renewed interest following the report in 1998 by Ebbesen and co-workers 13 of enhanced transmission through metallic films perforated with periodic arrays of subwavelength holes.…”
Section: Introductionmentioning
confidence: 99%
“…We find that a square-shaped grating does not offer a significant improved outcoupling efficiency over a thin (20 nm) thick metal layer, because the island-like surface roughness of the poly-crystalline deposited metal film (with an optimum thickness) already provides some momentum to facilitate outcoupling (Fig. 3e) [26,43]. Optimizing the grating up to about 40x times enhancement in light emission intensity was observed via the sine-shaped grating in comparison to the square shaped grating (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…[13][14][15][16][17][18] When the proton approaches the surface, a facial density e (r ʈ ) of the surface electrons is modified locally, so that they can screen the Coulomb potential of the proton. Therefore, it is possible for a surface plasmon to couple with a photon via local modulation in the facial electron density.…”
Section: Physical Interpretationmentioning
confidence: 99%